Involvement in Mental Health and Substance Abuse Work: Conceptions of Service Users - Minna Laitila; Merja Nikkonen; Anna-Maija Pietilä (Nursing Research and Practice)
Service user involvement (SUI) is a principal and a guideline in social and health care and also in mental health and substance abuse work. In practice, however, there are indicators of SUI remaining rhetoric rather than reality. The purpose of this study was to analyse and describe service users' conceptions of SUI in mental health and substance abuse work. The following study question was addressed: what are service users' conceptions of service user involvement in mental health and substance abuse work? In total, 27 users of services participated in the study, and the data was gathered by means of interviews. A phenomenographic approach was applied in order to explore the qualitative variations in participants' conceptions of SUI. As a result of the data analysis, four main categories of description representing service users' conceptions of service user involvement were formed: service users have the best expertise, opinions are not heard, systems make the rules, and courage and readiness to participate. In mental health and substance abuse work, SUI is still insufficiently achieved and there are obstacles to be taken into consideration. Nurses are in a key position to promote and encourage service user involvement.